Advanced Machining of Joint Implant UHMWPE Inserts - Píška, Miroslav; Urbancová, Kateřina (MDPI, 2022)
The modern orthopaedic implants for applications in hips, knees, shoulders, and spines are composed of hard metal alloys or ceramics and a tribological sub-component that is made of soft materials, with good frictional properties—e.g., UHMWPE (Ultra High Molecule Weight Polyethylene). The UHMWPE implants need to be machined into their final shape after the polymerization and consolidation into a blank profile or near net shaped implant. Thus, machining is a crucial technology that can generate an accurate and precise shape of the implant that should comply with the joints’ function. However, the machining technology can affect the topography and integrity of the surface, transmitted stresses, and resistance to wear. Technology, cutting tools, and cutting conditions can have an impact on the physical and mechanical properties of the entire implant and its longevity. This paper shows an effective and competitive technology for acquiring high-quality insert shape, dimensions, and surface, needed especially for customized implants.

The modern orthopaedic implants for applications in hips, knees, shoulders, and spines are composed of hard metal alloys or ceramics and a tribological sub-component that is made of soft materials, with good frictional properties—e.g., UHMWPE (Ultra High Molecule Weight Polyethylene). The UHMWPE implants need to be machined into their final shape after the polymerization and consolidation into a blank profile or near net shaped implant. Thus, machining is a crucial technology that can generate an accurate and precise shape of the implant that should comply with the joints’ function. However, the machining technology can affect the topography and integrity of the surface, transmitted stresses, and resistance to wear. Technology, cutting tools, and cutting conditions can have an impact on the physical and mechanical properties of the entire implant and its longevity. This paper shows an effective and competitive technology for acquiring high-quality insert shape, dimensions, and surface, needed especially for customized implants.
Advanced Machining of Joint Implant UHMWPE Inserts
Keywords: machining; UHMWPE; implant; surface integrity; tribology; machining; UHMWPE; implant; surface integrity; tribology